2005
DOI: 10.1093/bjaceaccp/mki042
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative electrolyte and fluid balance

Abstract: Appropriate fluid therapy is essential to protect organ function in the perioperative period. The physiological principles of fluid and electrolyte management are well described but a gap exists between knowledge and clinical practice. In this article, we will review fluid and electrolyte physiology, the stress response to surgery and hypovolaemia, and the consequences of electrolyte disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Similar changes in these parameters have been previously reported in dogs that underwent femorotibial joint surgery (Sibanda et al, 2006). The catabolic phase following trauma is characterized by increased anti-diuretic hormone and aldosterone secretion with consequent water and salt retention (Rassam & Counsell., 2005;Lobo et al, 2013). This causes the expansion of the extracellular fluid leading to haemodilution and drop in haematocrit (Lobo et al, 2013).…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Similar changes in these parameters have been previously reported in dogs that underwent femorotibial joint surgery (Sibanda et al, 2006). The catabolic phase following trauma is characterized by increased anti-diuretic hormone and aldosterone secretion with consequent water and salt retention (Rassam & Counsell., 2005;Lobo et al, 2013). This causes the expansion of the extracellular fluid leading to haemodilution and drop in haematocrit (Lobo et al, 2013).…”
Section: Resultssupporting
confidence: 67%
“…However, apart from the fall in K+, Na+, venous gas analysis performed during this study showed that pH, PaCO 2 , HCO 3 -and base excess significantly increased in the perioperative period. These findings suggested a state of metabolic alkalosis (Pettifer, 2003;Rassam & Counsell, 2005). It has been established that the body tries to control alkalosis through buffering as well as by respiratory compensatory mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These derangements can result in anorexia, nausea, muscle weakness, paralytic ileus, and cardiac conduction abnormalities, all or any of which can contribute to increased postoperative morbidity and mortality. 3 Once identified, derangements, such as hypokalaemia and hypocalcaemia are readily corrected with supplementation. The cases of hyperkalaemia observed were mild, but without routine testing, severe hyperkalaemia (> 7 mmol/L) cases, leading to life-threatening cardiac arrhythmias, may be missed.…”
Section: Discussionmentioning
confidence: 99%